L-arginine regulates mitochondrial function and oxidative stress in the acute kidney injury model of unilateral ureter obstruction - Seyed Mohammad Amin Kashani; Narges Abdoli; Forouzan Khodaei; Zahra Honarpishefard; Tahereh Golzar; Nazi Dastkhosh; Azad Salimi; Negar Azarpira; Hossein Niknahad; Reza Heidari (Trends in Pharmaceutical Sciences)
Acute kidney injury (AKI) is a significant clinical problem associated with high morbidity and mortality. Unilateral ureter obstruction (UUO) is a well-established model for studying the pathophysiology of AKI. L arginine (ARG), a precursor of nitric oxide, has been shown to possess renoprotective properties. This study aims to investigate the protective effects of ARG in an animal model of UUO-induced AKI. Male BALB/c mice were randomly allotted into sham-operated, UUO, and UUO + L-Arginine. UUO was surgically induced by ligating the left ureter. The treatment group received ARG (100, 250, and 500 mg/kg/day) intraperitoneally for seven days post-UUO surgery. Renal function was assessed by measuring plasma creatinine (Cr) and blood urea nitrogen (BUN) levels. Mitochondrial function was evaluated by determining mitochondrial membrane potential, dehydrogenases activity, and mitochondrial swelling. Oxidative stress markers, including ROS formation, lipid peroxidation, protein carbonylation, and tissue antioxidant capacity, were also measured in the kidney tissue. UUO led to significant renal dysfunction, as evidenced by increased serum Cr and BUN levels (P<0.001). Mitochondrial dysfunction was indicated by decreased mitochondrial dehydrogenase activity, mitochondrial depolarization, and increased mitochondrial swelling (P<0.001). Additionally, UUO-induced oxidative stress was demonstrated. It was found that ARG treatment significantly improved renal function by modulating mitochondrial function and decreasing oxidative stress markers (P<0.05). These findings suggest that ARG may have therapeutic potential in managing AKI by preserving mitochondrial function and reducing oxidative damage.